The herbaceous layer in forests of eastern North America - Gilliam, Frank S., 1954-; Roberts, Mark R., 1950- (Oxford University Press, 2003)
Focusing on the herbaceous layer of eastern forests, this volume combines perspectives from different levels of biological organization (ecophysiology to ecosystems) and forest types (from the eastern boreal forest to southeastern pine forests) into a synthesis of our knowledge of the ecology.